Establishment and application of a high-throughput screening model for cell adhesion inhibitors - Sun, Han; Wang, Xue-Kai; Li, Jian-Rui; Tang, Mei; Li, Hu; Lei, Lei; Li, Hong-Ying; Jiang, Jing; Li, Jia-Yu; Dong, Biao; Jiang, Jian-Dong; Peng, Zong-Gen (Frontiers in Pharmacology, 2023)
The cell adhesion between leukocytes and endothelial cells plays an important balanced role in the pathophysiological function, while excessive adhesion caused by etiological agents is associated with the occurrence and development of many acute and chronic diseases. Cell adhesion inhibitors have been shown to have a potential therapeutic effect on these diseases, therefore, less toxic and more effective inhibitors against cell adhesion are highly desirable. Here, using lipopolysaccharide-induced human umbilical vein endothelial cells (HUVECs) and calcein-AM-labeled human monocytic cell THP-1, we established a high-throughput screening model for cell adhesion inhibitors with excellent model evaluation parameters. Using the drug repurposing strategy, we screened out lifitegrast, a potent cell adhesion inhibitor, which inhibited cell adhesion between HUVEC and THP-1 cells by directly interrupting the adhesion interaction between HUVEC and THP-1 cells and showed a strong therapeutic effect on the mouse acute liver injury induced by poly(I:C)/D-GalN. Therefore, the screening model is suitable for screening and validating cell adhesion inhibitors, which will promote the research and development of novel drugs to treat inflammatory diseases caused by excessive cell adhesion.